Perancangan Sistem E-Commerce Berbasis OpenChart untuk Meningkatkan Strategi Promosi Pada Home Industry Produk Kue Kering Di Kecamatan Panyabungan - Nabilah, Rizky; Annas, Firdaus; Syahrani, Selfira (JOVISHE : Journal of Visionary Sharia Economy, 2024)
This article discusses system planning to improve promotional strategies in the Home Industry in panyabungan District. This design uses Opencart, a web-based e-commerce platform, asa modern solution to traditional promotions which are still limited. Currently, promotion of Home Industry products in this area is only carried out conventionally and marketing reach is still limited around panyabungan District. In fact, with technological developments and the rapid ise of online marketing, promotional strategies should adapt to the needs of the times. With this research, the aim is to change traditional promotional methods to technology-based ones through Opencart. This research uses the Research and Development (R&D) method with the Define, Design, Develop, and Dissemination development model. The final result of this research is an e-commerce system in the form of web-based promotional media that utilizes the openchart application. The findings from this research, where promotional media using Opencart which has been designed will be a support for incrasing competitiveness in Home Industry products in Panyabungan District. The implications of this research show that the implementation of web-based technology such as Opencart not only expands product marketing reach but can also openup opportunities to increase sales significantly. This system also provides local business actors with ease in managing catalogues, orders and payments, so they can be more efficient and effective in facing competition in today’s digital era.